BN/Ag hybrid nanomaterials with petal-like surfaces as catalysts and antibacterial agents - Firestein, Konstantin L.; Leybo, Denis V.; Steinman, Alexander E.; Kovalskii, Andrey M.; Matveev, Andrei T.; Manakhov, Anton M.; Sukhorukova, Irina V.; Slukin, Pavel V.; Fursova, Nadezda K.; Ignatov, Sergey G.; Golberg, Dmitri V.; Shtansky, Dmitry V. (Beilstein Journal of Nanotechnology, 2018)
BN/Ag hybrid nanomaterials (HNMs) and their possible applications as novel active catalysts and antibacterial agents are investigated. BN/Ag nanoparticle (NP) hybrids were fabricated using two methods: (i) chemical vapour deposition (CVD) of BN NPs in the presence of Ag vapours, and (ii) ultraviolet (UV) decomposition of AgNO3 in a suspension of BN NPs. The hybrid microstructures were studied by high-resolution transmission electron microscopy (HRTEM), high-angular dark field scanning TEM imaging paired with energy dispersion X-ray (EDX) mapping, X-ray photoelectron spectroscopy (XPS), and infrared spectroscopy (FTIR). They were also characterized in terms of thermal stability, Ag+ ion release, catalytic and antibacterial activities. The materials synthesized via UV decomposition of AgNO3 demonstrated a much better catalytic activity in comparison to those prepared using the CVD method. The best catalytic characteristics (100% methanol conversion at 350 °C) were achieved using the UV BN/Ag HNMs without preliminary annealing at 600 °C in an oxidizing atmosphere. Both types of the BN/Ag HNMs possess a profound antibacterial effect against Escherichia coli K-261 bacteria.
Keywords: antibacterial agents; BN/Ag hybrid nanomaterials; catalysts; chemical vapour deposition; nanomaterials